Efficacy and tolerability of perampanel in patients with seizures in real-world clinical practice: A systematic review and meta-analysis - Hou, Liyan; Yang, Jingjing; Zhang, Xuan; Li, Na; Li, Sheng; Zhang, Lei; Zhao, Jie; Wang, Qingshan (Frontiers in Pharmacology, 2023)
Objectives: The aim of this study was to systematically review the efficacy and tolerability of perampanel (PER) that was used as add-on treatment or monotherapy in patients with epilepsy aged 12 years and older in routine clinical practice. Methods: Electronic and clinical trials databases were searched for observational studies of PER published up to 1 March 2022. Outcomes of interest were responder rate, adverse effects (AEs) and withdraw rate. Subgroup analysis were performed to explore the potential factors that might affect the efficacy and safety of PER. Results: Fifty-six studies including 10,688 patients were enrolled. Results showed that after 3, 6 and 12 months of PER treatment, the pooled 50% responder rates in patients with epilepsy were 50.0% (95%CI: 0.41-0.60), 44.0% (95%CI: 0.38-0.50) and 39.0% (95%CI: 0.31-0.48), respectively and the pooled seizure-free rates were 24.0% (95%CI: 0.17-0.32), 21.0% (95%CI: 0.17-0.25) and 20.0% (95%CI: 0.16-0.24), respectively. Subgroup analysis revealed that the efficacy of PER could be affected by the way of PER administration. Patients in groups that the PER was used as first add-on, primary monotherapy or combined with non-enzyme-inducing AEDs (non-EIAEDs) displayed high 50% responder rate and seizure-free rate compared with patients in late add-on, conversion therapy or combined with EIAEDs groups, respectively. Furthermore, the incidences of AEs at 3, 6 and 12 months of PER treatment were 46% (95%CI: 0.38-0.55), 52.0% (95%CI: 0.43-0.60) and 46.0% (95%CI: 0.40-0.52), respectively. The withdrawal rates due to AEs were 8.0% (95% CI: 0.06-0.11), 16.0% (95% CI: 0.13-0.20) and 16% (95% CI: 0.11-0.21) at 3, 6 and 12 months of PER treatment. Subgroup analysis showed a higher withdraw rate in the rapid (30%, 95% CI: 0.22-0.38) than that of the slow titration group (12%, 95% CI: 0.06-0.18). Conclusion: Altogether, PER was effective and could be fairly tolerated in both short-term and long-term usage in epilepsy patients in routine clinical practice. Furthermore, PER appeared to be more effective when PER was used as first add-on, monotherapy, or concomitant with non-EIAEDs.